Providing Access Isolation to Information in the Database - Arman, Akanov; Kakim, Sagindykov (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Most modern database management systems (DBMS) provide the ability to restrict user access to database objects. The problems of restricting access to individual records are arising increasingly in connection with the growing need for flexibility in restricting access in modern databases, including when using them to store information classified as state or commercial secrets. Currently, these tasks are solved individually, and there are no commonly formalized approaches to designing such access restrictions. The study aims to reduce the design time for database schemes when it is necessary to restrict access to individual records of the database tables and improve the quality of the designed schemes by using the proposed algorithms. Questions about the design of the protected databases with the use of access restrictions to separate records are considered. Both restriction of illegal access to records, and granting false camouflage information instead of required is considered. The proposed software package will consist of 2 main parts: a database and a client application. To differentiate access, the study proposed the use of a record-protecting lock.